TNM Supplement 1993 A Commentary on Uniform Use - Hermanek, P.; Henson, D. E.; Hutter, R. V. P.; Sobin, L. H. (Springer Berlin Heidelberg, 1993)
The fourth edition of the TNM Classification was published in 1987,1 and a revision in 1992.2 It was the result of efforts by all national TNM Committees towards a worldwide uniform classification. The classifica tion criteria are identical with the fourth edition of the Manual for 3 Staging of Cancer of the American Joint Committee on Cancer (AJCC). Although the classification has found wide acceptance, some workers have pointed out that individual definitions and rules for staging are not sufficiently detailed. This can lead to inconsistent application of the clas sification. the antithesis of standardization. This source of differences in interpretation applies not only to the classification of individual organs but also to the general rules of the system, especially to the definitions of the requirements for the pathological classification (pT, pN). These are specified only for carcinoma of the breast; for other sites, reference must be made back to the general rules. which can lead to variable interpreta tions. The TNM Project Committee of the UICC has addressed this prob lem and collected and considered the criticisms and suggestions from the national TNM Committees as well as from cancer registries, oncolo gical associations and individual users. The result was the decision to complement the 4th edition of the TN M Classification 1.2. 3 with the publi cation of a TNM Supplement containing recommendations for the uni form use of TNM.
Keywords: Oncology; Pathology; Radiotherapy; Oncology; Tumorklassifikation; TNM-System